The Effect of Multiball and Shadow Training Methods on Forehand Push Accuracy in Table Tennis Extracurriculars - Aulia, Salsa Najwa; Bachtiar, Bachtiar; Maulana, Firman (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
This study aims to determine the accuracy of forehand push in extracurricular table tennis at SDN Cibatu Nagrak. The method used in this research uses quantitative methods with Nonequivalent control group design. The research population of table tennis extracurricular members at SDN Cibatu Nagrak, totaling 12 people. Samples taken 12 people with saturated sampling techniques, namely techniques where all members of the population are sampled. The instruments used are (1) training program, (2) forehand push accuracy test. Based on the results of data analysis conducted, that in this study has a significant effect, seen from the paired sample t test obtained multiball significance value of 0.000 with a significance level <0.05, and obtained from shadow significance with a significance level <0.05, it can be concluded in this study that there is an effect of training using multiball and shadow on the accuracy of forehand push on extracurricular table tennis at SDN Cibatu Nagrak, and multiball training is better than shadow because the percentage increase of multiball is 15.56% while shadow is 12.79%.